2004
DOI: 10.1111/j.0962-1075.2004.00504.x
|View full text |Cite
|
Sign up to set email alerts
|

Activity and sequence characterization of two cysteine proteases in the digestive tract of the reduviid bug Triatoma infestans

Abstract: Cathepsin B- and cathepsin L-like activities were identified in gut extracts of the blood-sucking bug Triatoma infestans using specific substrates and inhibitors. Activities decreased during the first 2 days after feeding but increased to a maximum value at 5 and 10 days post feeding. The deduced 332 and 328 amino acid sequences showed high levels of identity (50-60%) to other insect cathepsin B- and L-like proteases, respectively. The three amino acid residues of the catalytic domain, CHN, and the GCNGG motif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
39
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 60 publications
(99 reference statements)
0
39
0
Order By: Relevance
“…The following degenerate primers were designed according to the amino acid residues flanking the His and Ser of the active site of serine proteinases (Sakanari et al 1989;Elvin et al 1993 (Kollien et al 2004b). Only the annealing parameters in a Hybaid (Omni Gene) thermal cycler (Hybaid, Ashford, Middx, UK) differed (54.2, 55.5, 56.9, 58.4, 59.3 and 59.8°C).…”
Section: Rna and Genomic Dna Isolationmentioning
confidence: 99%
See 3 more Smart Citations
“…The following degenerate primers were designed according to the amino acid residues flanking the His and Ser of the active site of serine proteinases (Sakanari et al 1989;Elvin et al 1993 (Kollien et al 2004b). Only the annealing parameters in a Hybaid (Omni Gene) thermal cycler (Hybaid, Ashford, Middx, UK) differed (54.2, 55.5, 56.9, 58.4, 59.3 and 59.8°C).…”
Section: Rna and Genomic Dna Isolationmentioning
confidence: 99%
“…To exclude Try1-cDNA, which contains an EcoRI restriction site at the positions 373-378 in the cDNA sequence, the PCR product was digested with EcoRI, separated on a 1% agarose-gel, and again a 470 bp fragment was cloned (Kollien et al 2004b). …”
Section: Rna and Genomic Dna Isolationmentioning
confidence: 99%
See 2 more Smart Citations
“…In the beginning of the 1980s activities of cathepsin B and D, aminopeptidase and carboxypeptidase have been shown [16,17]. Later, when the appropriate molecular biology methods were available, different isoforms of genes from different triatomine species have been identified encoding cathepsin B, L and D and serine carboxypeptidase [18][19][20][21][22]. At the same time Borges et al [23] have demonstrated a significant increase of cathepsin D activity in Rhodnius prolixus infected with T. cruzi.…”
mentioning
confidence: 99%